Discussion of "Challenges in operationalizing the water–energy–food nexus"*. Issue 12 (10th September 2018) - Nauditt, Alexandra
ABSTRACT: In their opinion paper, Liu et al . highlight the insufficient development of methods such as integrated modelling tools to assess the water–energy–food (WEF) nexus system complexity. This can be attributed to the lack of research programmes addressing the WEF nexus, especially in the European Union. To enable the development of innovative research methods, we need educational and research programmes that explicitly focus on the WEF security nexus. These programmes should promote interdisciplinary approaches that incorporate hydrology as well as sciences related to energy and food security, and environmental governance.